ORAL CONTROLLED RELEASE MATRIX FORMULATION DESIGN AND THEIRRATE CONTROLLING FACTORS - Maria Ashfaq et al (Baqai Journal of Health Sciences)
The trend of formulation development of controlled release (CR) matrix drug delivery system has been increased to many folds during the last few years. Such CR dosage forms are now considered to be more effective than conventional immediate release dosage formulations due to avoidance of frequent dose administration with precise drug release over an extended time period. A properly formulated matrix based system also offers targeted delivery to a selected organ/tissue where the drug release is controlled at a specific rate. Development of matrix-based tablets with persistent drug release has always been a challenge to the pharmaceutical manufacturers owed to various biological, physicochemical and release limiting factors. In this review, different types of matrix-based systems are discussed in detail. Parameters that greatly influence the release of active pharmaceutical ingredient (API) from the matrix design and would eventually affect the overall performance of such products are also been highlighted